The Negotiation of Quality Standards: Social Interactionist Approach to Fruit and Vegetable Distribution in Argentina - Laura Viteri , Maria; Arce, Alberto (The International Journal of Sociology of Agriculture and Food, 2013)
This article addresses food quality standards. It suggests that writing on standards creates a flat view of the subject, failing to grasp the richness of the multiple self-organizing practices that shape quality within functioning markets. The article documents the social dimension of quality and the ‘quality strategies’ developed by fresh-food wholesalers, greengrocers and producers in the Buenos Aires Wholesale Central Market, Argentina. These strategies assemble the freshfood market and construct a representation of quality as an aspect of trade in places where food exchanges are conducted. Using a social interactionist approach, we propose that attention needs to be given to the settings in which food quality standards are negotiated and used by different actors. In so doing we suggest that studies that focus on the diffusion of ‘global’ quality standards should not omit consideration of differential responses to these standards, even if the conditions appear relatively homogeneous.